STRATEGI HUMAS PLN TEMPEH DALAM MENINGKATKAN CITRA PERUSAHAAN - Fadia Bella Rossita (Universitas Muhammadiyah Jember, 2023)
As the only company assigned responsibility in the field of National electricity. PLN (Persero) is one of the companies owned by State-Owned Enterprises (BUMN) which is engaged in the provision of electricity, telecommunications, and is also the most influential and surviving company in Indonesia. PLN is one of the electricity agents who are very closely related, tasked with developing business activities related to electricity with the aim of improving people's welfare and also encouraging economic improvement. A company certainly really needs the existence of public relations, because public relations has a very important role and task. PLN continues to strive to create new strategies and innovations in satisfying customers and continues to pay attention to improving services to customers. The success of PLN is largely determined by the success of a public relations officer in maintaining a positive reputation or image in the community. This study uses qualitative research with data collection techniques, namely interviews and literature study with data analysis using data reduction steps, data presentation and data verification. The data obtained is by getting actual data and facts. In this research, the theory used is image theory. The results of the research obtained are knowing PLN's public relations strategy in improving the company's image through electronic media and social media and also PLN presents an application that can facilitate the community, namely PLN Mobile. And also knowing how the community's response to the strategy that has been carried out by PLN's public relations, the response given by the community is very positive towards applications that make it easier for customers to pay for prepaid and postpaid electricity, they can also activate notifications about power outages